INNOVATION IN THE ASSESSMENT OF MAHARAH KITABAH BASED ON AKM ARABIC BOOKS KEMENAG - Nada Nabilah Syafiqoh; R. Umi Baroroh; Tasha Ayu Az-Zahra; Moh Paris Fauzi Sawedi (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
The goal of this study is to be creative in assessing Maharah Kitabah using AKM. This research employs descriptive qualitative methods. The data source used is secondary data, with data collection techniques such as documentation and qualitative data descriptions. The goal is to generate innovation in the Maharah Kitabah assessment based on AKM. The conclusion in the article is to discuss the assessment of learning Arabic, especially Maharah Kitabah. Assessment is carried out to determine the ability of students regarding Maharah Kitabah. Where the assessment on Maharah Kitabah is innovated using an assessment rubric adhering to a minimum competency assessment.